Great food presentation : a practical guide - Video Education Australasia (Bendigo, Vic.: Video Education Australasia, 2022)
Julien Jane demonstrates how to imaginatively present soup, sushi, pastry and terrine entree platters, main courses and dessert. She shows us how to make the best use of available resources, and how small, thoughtful touches can enhance almost any food presentation.